Photoactivatable nanoagonists chemically programmed for pharmacokinetic tuning and in situ cancer vaccination - Wan, Jianqin (2023)
Immunotherapy holds great promise for the treatment of aggressive and metastatic cancers; however, currently available immunotherapeutics, such as immune checkpoint blockade, benefit only a small subset of patients. A photoactivatable toll-like receptor 7/8 (TLR7/8) nanoagonist (PNA) system that imparts near-infrared (NIR) light-induced immunogenic cell death (ICD) in dying tumor cells in synchrony with the spontaneous release of a potent immunoadjuvant is developed here. The PNA consists of polymer-derived proimmunoadjuvants ligated via a reactive oxygen species (ROS)-cleavable linker and polymer-derived photosensitizers, which are further encapsulated in amphiphilic matrices for systemic injection. In particular, conjugation of the TLR7/8 agonist resiquimod to biodegradable macromolecular moieties with different molecular weights enabled pharmacokinetic tuning of small-molecule agonists and optimized delivery efficiency in mice. Upon NIR photoirradiation, PNA effectively generated ROS not only to ablate tumors and induce the ICD cascade but also to trigger the on-demand release of TLR agonists. In several preclinical cancer models, intravenous PNA administration followed by NIR tumor irradiation resulted in remarkable tumor regression and suppressed postsurgical tumor recurrence and metastasis. Furthermore, this treatment profoundly shifted the tumor immune landscape to a tumoricidal one, eliciting robust tumor-specific T cell priming in vivo. This work highlights a simple and cost-effective approach to generate in situ cancer vaccines for synergistic photodynamic immunotherapy of metastatic cancers.